George Mackenzie of Cromarty's Synopsis Apocalyptica (1708): A New Analysis. Issue 1 (April 2023) - Corrigan, Alexander
Abstract : This article offers the first detailed analysis of George Mackenzie of Cromarty's most explicitly theological work, the 1708 Synopsis Apocalyptica . It includes critical engagement with the text, consideration of its polemical aims and targets, and comparison to its major influences. It contends that the Synopsis is crucial to understanding Mackenzie's ideas and motivations, revealing for the first time, the religious, eschatological connections between Mackenzie's unionism, monarchism and opposition to deism, atheism and Judaism. The Synopsis betrays more than previously unnoticed Judeophobia on Mackenzie's part; it illustrates that a distinct form of anti-Jewish bigotry which cast Jews as dangerous, cruel oppressors of Christians was present in the British Isles throughout the long seventeenth century. The article therefore cautions against the assumption that the dawn of the eighteenth century was necessarily characterised by increased religious toleration amongst educated elites.